STUDI KOMPARATIF PENGATURAN STANDARISASI DI INDONESIA DAN TAIWAN TERHADAP PRODUK MIE INSTAN - Nabila Putri Khoirunnisa (2023)
Consumers as users of products should need a guarantee of safety for the consumption of a product. Producers in marketing their products must pay attention to consumer rights in order to carry out business activities that have ethics and responsibility. Food is a basic need in a person and its fulfillment is a component of human rights as a fundamental part of creating human resources with good quality. The state is also obliged to create affordability, availability, and meet food consumption safely, adequately, quality, and have balanced nutrition. In this case, it was found that the food quality standards owned by the Indonesian government and the Taiwanese government have differences in the provisions of the safe limit of substances in preservatives, in this regard Indonesia uses BPOM standards and Indonesia is a member of the Codex Alimentarius Commission (CODEX) Alimentarius Commission (CAC) which has obtained international recognition. However, this condition is a conflict because Taiwan applies a different standard, namely the prohibition of Methyl P-Hydroxybenzoate in food products. In addition, Taiwan did not join the CODEX, which resulted in Indomie products being banned from circulation in Taiwan and Hong Kong. This study was made with the intention of comparing standardization settings in Indonesia and Taiwan with instant noodle products. This research method uses a normative juridical approach method, namely the author examines and studies the norms contained in laws and regulations and other norms based on Law Number 8 of 1999 related to consumer protection.